IMPLEMENTASI AKAD MUDHARABAH MUTLAQAH TERHADAP PRODUK SIMPANAN HAJI DAN UMROH (SAHARA) DI KSPPS BMT NU JAWA TIMUR CABANG SUMBERSARI JEMBER - Hali Makki; Mahmud Yunus Mahmud Yunus (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Islamic financial institutions in the midst of society have an important role in helping meet community needs, and one of them is in the field of service needs, especially in Hajj and Umrah savings. Islamic Finance institutions or commonly referred to as BMTs or Banks, because BMTs already have activities to collect public funds and can distribute and manage them, collect funds from customers or members, especially in Hajj and Umrah savings, which can later be utilized for needsthe community, and this requires terms and conditions that have been provided by the BMT or the Bank, while the BMT NU already has a plan that has been designed at the BMT NU Sumbersari Jember Branch to achieve common goals, on the other hand the BMT NU Sumbersari Branch has very good productsgood in sharia principles.at BMT NU, the Sumbersari Branch itself has a product that makes it very easy for customers to perform the Hajj and Umrah pilgrimage, namely the SAHARA Savings. where the savings use a mudharabah mutlaqah contract with profit sharing and the initial deposit from the savings so that subsequent deposits are in accordance with the capabilities of the customer. To facilitate understanding in research, researchers use research methods including: digging up and digging up data sources that can provide complete information. By using data analysis methods, namely data reduction, data presentation and verification.